People with progressive visual impairments in the open labor market – an analysis of the career trajectories of employees with Stargardt disease - Kokot-Rybińska, Magdalena (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
According to various data, there are around 2 million people in Poland with various types of vision impairments. Vision impairment ranks as the fourth cause of disability in the country (GUS, 2019). In most cases, significant deterioration of visual function occurs after completing education and choosing a career path. The aim of the conducted research was to determine in which industries and professions individuals with progressive visual impairments work. The research problem consisted of two elements: on the one hand, determining the specific professions performed by individuals with progressive vision dysfunction, and on the other hand, identifying the potential difficulties faced by such employees. For this reason, it was decided to use a survey measurement, where participants could indicate the profession they work in or write their own if it was not on the list. On the other hand, some of the respondents (20 out of 50 individuals) participated in in-depth interviews regarding their functioning with progressive eye disease. By using techniques such as open-ended questions and encouraging storytelling, it was possible to gather interesting research material. After collecting all the interviews, narrative analysis was additionally applied to elucidate the most important issues centered around three main questions.